1994
DOI: 10.1088/0268-1242/9/11/016
|View full text |Cite
|
Sign up to set email alerts
|

Spray pyrolysis deposition of SnxSythin films

Abstract: Tin sulphide (Sn,S,) thin films have been prepared on Pyrex glass substrates by the spray pyrolysis technique using tin chloride (SnCl,) and n, ndimethylthiourea (CH3NHCSNHCH3) as starting materials. The depositions were carried out in the range of substrate temperatures from 320 to 450 "C. From x-ray diffraction measurements and SEM micrographs, it is found that the values of x and y, which determine the type of deposited compound, depend on the substrate temperature. At lower substrate temperatures (320-360 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 24 publications
(3 reference statements)
2
38
0
Order By: Relevance
“…The authors have observed, in agreement with the reports of Lopez et al [45] and Thangaraju et al [46], that Sn-S compounds are predominant for sulfurisation temperatures superior to 300 • C. Koteeswara-Reddy et al [47] stated similarly that Sn x S y films grown at high temperatures were nearly stoichiometric in nature with an elemental Sn/S ratio of 1.03. In fact, under high temperatures, the Sn-O bonds are weakened inside the structure (Fig.…”
Section: Discussion and Perspectivessupporting
confidence: 85%
“…The authors have observed, in agreement with the reports of Lopez et al [45] and Thangaraju et al [46], that Sn-S compounds are predominant for sulfurisation temperatures superior to 300 • C. Koteeswara-Reddy et al [47] stated similarly that Sn x S y films grown at high temperatures were nearly stoichiometric in nature with an elemental Sn/S ratio of 1.03. In fact, under high temperatures, the Sn-O bonds are weakened inside the structure (Fig.…”
Section: Discussion and Perspectivessupporting
confidence: 85%
“…As-deposited SnS films exhibited activation energy of 0.121 eV. The activation energy of the SnS films is attributed to shallow acceptor states due to Snvacancies [5,17]. These Sn vacancies are characteristics of IV-VI compounds that play a significant role in establishing the p-type conductivity of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Devica et al [7] reported an activation energy of 0.26 eV for thermal evaporation SnS films, Noguchi et al [18] observed the activation energy between 0.28 eV and 0.34 eV in thermal evaporated SnS films. Lopez et al [17] reported an activation energy of 0.54 eV for sprayed SnS films. Therefore, the activation energy of the SnS films depends on the film thickness, the preparation technique and the film composition.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been made in our previous work, reported elsewhere, and by other workers. [10][11][12][13][14] The behaviour is presented in Fig. 4.…”
Section: Structural Analysismentioning
confidence: 99%